Higher prevalence of migraine in essential tremor: A case–control study. (December 2014) - Hu, Yueqing; Tang, Wenjing; Liu, Ruozhuo; Dong, Zhao; Chen, Xiaoyan; Pan, Meiyan; Yu, Shengyuan
Background: The existence of an association between migraine and essential tremor has long been controversial. The prevalence of migraine in essential tremor patients was surveyed to explore the association between the two diseases. Methods: A case–control clinical study was conducted to investigate the prevalence of migraine in 150 consecutive essential tremor patients and in 150 matched controls without tremor. Detailed information about essential tremor and migraine was obtained using a structured questionnaire at a face-to-face interview. Moreover, a functional variant of the dopamine receptor D3 gene (Ser9Gly, rs6280) was studied in 46 essential tremor patients with and without migraine using direct sequencing analysis. Results: The prevalence of lifetime migraine in essential tremor patients was significantly higher than that in controls (22.0% vs. 12.7%; p  = 0.035; odds ratio = 1.95; 95% confidence interval = 1.05–3.60). No significant difference was found in the migraine features between the essential tremor and control groups and most tremor characteristics were no different in essential tremor patients with and without migraine. A higher male prevalence of essential tremor patients without migraine was observed. Moreover, 44 of 46 (95.7%) essential tremor patients had the dopamine receptor D3 Ser9Gly variant, but no significant difference was found in the frequencies of the variant between essential tremor patients with and without migraine (87.5% vs. 100.0%; p  = 0.22). Conclusion: Our data suggest that essential tremor patients have a higher risk of lifetime migraine than do controls and the dopamine receptor D3 Ser9Gly variant may be lower in essential tremor with migraine than the general essential tremor patients.